Mobility of the LGP-30 wheeled vehicle on peat terrain in Malaysia - Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Hossain, Altab; Noraini, N.; Irwan, I. (2007)
The Low Ground Pressure (LGP-30) wheel vehicle was tested on the 17 kN/m2 low bearing capacity peat terrain in Malaysia. The number of field test was conducted at three different traveling speeds of 6 km/h, 10 km/h and 12 km/h by mounting the developed torque transducer with the vehicle. The sensitivity of the designed and developed torque transducer was found 20.04 mV/V per Nm. The mean value of the test results on tractive effort was found 11.66 kN, 9.89 kN and 9.06 kN for the travelling speed of 6 km/h, 10 km/h, and 15 km/h, respectively.